1997
DOI: 10.1007/bf03026139
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of electrochemically and chemically investigated corrosion behaviors of 316L SS in acid chloride environments

Abstract: The electrochemical behavior of 316L stainless steel was investigated in acid chloride environments, and pitting potentials were determined electrochemically and chemically. An increase in the anodic maximum current density was observed upon decreasing the cathodic potential from which the scan was initiated to determine the polarization curve. To determine the critical pitting potential through the chemical method, the potential was increased by increasing the concentration of ferric ions in ferric chloride w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Attempt was also made to determine a correlation between the electrochemical and chemical methods [47]. Otero et al reported that, after studying the corrosion behavior of type 304L and 316L austenitic stainless steels in chloride containing solution with the concentration from 0.05 to 0.41 M, crevice corrosion was observed in the area close to pores and in some area of contact between powder particles [48].…”
Section: Coagulants Used In Water and Wastewater Treatmentmentioning
confidence: 99%
“…Attempt was also made to determine a correlation between the electrochemical and chemical methods [47]. Otero et al reported that, after studying the corrosion behavior of type 304L and 316L austenitic stainless steels in chloride containing solution with the concentration from 0.05 to 0.41 M, crevice corrosion was observed in the area close to pores and in some area of contact between powder particles [48].…”
Section: Coagulants Used In Water and Wastewater Treatmentmentioning
confidence: 99%
“…Attempt was also made to determine a correlation between the electrochemical and chemical methods[47]. Otero et al reported that, after studying the corrosion behavior of type 304L and 316L austenitic stainless steels in chloride containing solution with the concentration from 0.05 to 0.41 M, crevice corrosion was observed in the area close to pores and in some area of contact between powder particles[48].Dawson and Ferreira also observed crevice corrosion caused by the influence of chloride ion in solution.…”
mentioning
confidence: 99%